GREEN GOVERNANCE IN ACTION: REFLEKSI KRITIS ATAS IMPLEMENTASI PRINSIP GREEN BUSINESS MELALUI HUKUM LINGKUNGAN INDONESIA [GREEN GOVERNANCE IN ACTION: A CRITICAL REFLECTION ON THE IMPLEMENTATION OF GREEN BUSINESS PRINCIPLES THROUGH INDONESIA’S ENVIRONMENTAL LAW] - Nurbit, Nurbit; Rahmat, Hayatul Khairul; Sispurwanto, Yedi (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
The implementation of green business principles has increasingly become a strategic necessity for companies in Indonesia, particularly in response to rising regulatory pressures, global market demands, and the urgent need to safeguard environmental sustainability. Various environmental law instruments—such as the Environmental Protection and Management Act (PPLH), derivative regulations related to Environmental Impact Assessment (AMDAL), the PROPER performance rating program, and emission standards—provide a legal framework that indirectly drives the transformation of business practices toward greener models. This paper offers an in-depth discussion of the relationship between environmental regulation and the implementation of green business through a review of international and national literature. The discussion covers the dynamics of environmental law enforcement, challenges faced by industries in implementation, the role of green innovation, and Indonesia’s position in regional and global contexts. The findings indicate that the successful implementation of green business relies not only on strict regulations but also on organizational capabilities, technological support, market mechanisms, and government incentives. This study provides both theoretical and practical contributions on how environmental law can steer structural corporate changes toward sustainability.